Bancada digital didática para análise de flambagem: Desenvolvimento e Aplicação - Cavalcante, Igor Pinto (2024)
The work presents a proposal for the development and construction of a didactic buckling bench with digital resources for data acquisition. The aim is to create a teaching tool that offers a practical experience of Euler column buckling concepts for engineering students, driven by the desire to improve teaching methodology in universities. Additionally, the constructed bench provides a visual resource that simulates column compressions under different end conditions. To build the bench, knowledge of metal structures, machine elements, additive manufacturing, electrical systems, and programming was required. Stainless steel rulers were used, subjected to three types of upper and lower end conditions: articulatedarticulated; articulated-fixed; and fixed-fixed. Each of these conditions has a characteristic curvature and a critical buckling load, allowing for use in slender bodies with lengths between 15 cm and 35 cm, thicknesses up to 5 mm, and loads up to 20 kg. The system adopted a process of digitizing result readings, using load cells and an electronic acquisition board on the Arduino platform, with loading results displayed digitally